Sinyal Merek Sepatu Vans: Analisis Niat Beli dan Peran Key Opinion Leader - Marsinda Apriliana; Adhi Prakosa; Fikri Farhan (JURNAL RISET MANAJEMEN (JURMA), 2026)
The sneaker industry in Indonesia has experienced significant growth as fashion has taken on an increasingly important role as part of lifestyle and a means of self-expression, particularly among the younger generation. Amid intensifying brand competition, companies must not only rely on product quality but also build strong brand signals through brand image, brand identity, and brand engagement to boost consumer purchase intent. Additionally, the presence of relevant and credible key opinion leaders (KOLs) is considered capable of strengthening the effectiveness of these brand signals. This study aims to analyze the influence of brand image, brand identity, and brand engagement on the purchase intention for Vans shoes in the Special Region of Yogyakarta (DIY), as well as to test the moderating role of KOL Voice of Baceprot’s awareness. This study employs a quantitative approach using a survey method with 154 respondents; the data were analyzed using the PLS-SEM method. The results indicate that brand image and brand engagement have a significant effect on purchase intention, whereas brand identity does not have a significant effect. Furthermore, KOL awareness was not found to moderate the relationship between the independent variables and purchase intention.